2019
DOI: 10.3171/2017.12.jns171681
|View full text |Cite
|
Sign up to set email alerts
|

Changes in language white matter tract microarchitecture associated with cognitive deficits in patients with presumed low-grade glioma

Abstract: OBJECTIVE The authors conducted a study to determine whether cognitive functioning of patients with presumed low-grade glioma is associated with white matter (WM) tract changes. METHODS The authors included 77 patients with presumed low-grade glioma who underwent awake surgery between 2005 and 2013. Diffusion tensor imaging with deterministic tractography was performed preoperatively to identify the arcuate, inferior frontooccipital, and uncinate fasciculi and to obtain the mean fractional anisotropy (FA) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 30 publications
(39 reference statements)
2
16
0
Order By: Relevance
“…This is somewhat in contrast with the findings of Incekara et al, who observed a deterioration in language functions after awake surgery of eloquently located presumed LGGs. Their smaller-scale study was mostly focused at left hemisphere brain regions, whereas our results represent a wider range of glioma patients [14]. Satoer et al, also found postoperative decline in language and executive functions.…”
Section: Discussionmentioning
confidence: 41%
“…This is somewhat in contrast with the findings of Incekara et al, who observed a deterioration in language functions after awake surgery of eloquently located presumed LGGs. Their smaller-scale study was mostly focused at left hemisphere brain regions, whereas our results represent a wider range of glioma patients [14]. Satoer et al, also found postoperative decline in language and executive functions.…”
Section: Discussionmentioning
confidence: 41%
“…In this retrospective cohort we did not have neurocognitive testing data available for these specific tracts to correlate our findings to neuro-cognitive performance. Recently however, using patients from the same cohort, a study was published on white matter tracts involved in language and attention showing a significant relationship between WM tract alterations and language and attention performance ( 69 ). In the future, an important question will be if the degree of subcortical volume loss correlates to the severity of neurocognitive deficits, our current database however lacks the outcome data to address this question.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the most common clinical manifestations, including nausea, headache, epilepsy, and neurological deficits, an increasing number of studies have shown that patients with gliomas may suffer impairments in multiple cognitive domains (Maesawa et al., 2015; Mariano, Mazza, & Galzio, 2013; Miotto et al., 2011). Gliomas have been reported to cause various degrees of white matter fiber damage (Incekara, Satoer, Visch‐Brink, Vincent, & Smits, 2018; Soni, Mehrotra, Behari, Kumar, & Gupta, 2017). In addition, gliomas are well recognized for their infiltrative growth along the white matter tracts (Louis, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…FA is commonly referred to as a summary measure of microstructural integrity of WM tracts and is a normalized standard deviation of the eigenvalue between 0 and 1. A reduced FA in a WM tract usually indicates a change in the integrity of the fiber bundle (Alexander et al., 2011; Incekara et al., 2018). Diffusion tensor tomography (DTT) evaluates water diffusion in the WM of the brain and shows subcortical tract integrity based on indices such as FA, mean diffusivity, and radial diffusivity.…”
Section: Introductionmentioning
confidence: 99%